Penerapan Model Project Based Learning Dalam Meningkatkan Hasil Belajar PAI di Kelas XI SMK Negeri 1 Guguk - Hasanah, Fitria (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to determine the effectiveness of applying the Project-Based Learning (PJBL) model in improving students’ learning outcomes in Islamic Religious Education at SMK Negeri 1 Guguk. The research was conducted in two cycles, each consisting of several meetings, including pre-test, project-based learning activities, and post-test. The results of the study show that the application of the PJBL model can improve students’ learning outcomes, both individually through the improvement of scores on pre-test and post-test, and in groups through project presentations that demonstrate an increase in creativity, communication, and teamwork among students. In Cycle II, the percentage of students achieving mastery reached 92.9%, indicating a significant improvement compared to Cycle I. This study concludes that the PJBL model is effective in improving students’ learning outcomes, although some challenges can be overcome with a firmer approach and intensive guidance from the teacher.